Awareness regarding medical ethics in health care practice among the resident doctors in a tertiary care hospital of the sub-Himalayan region: a cross sectional study - Parashar, Anupam; Chauhan, Nidhi; Gupta, Rahul; Kumar, Vineet (International Journal Of Community Medicine And Public Health, 2019)
Background: Bio-ethics i.e. health care ethics is a set of moral principles, beliefs and values that guide us in making choices about medical care. This novel study was carried out with an objective of assessment of knowledge regarding the medical ethics among the resident doctors of Indira Gandhi Medical College, Shimla Himachal Pradesh. Methods: This descriptive analytical cross-sectional study was conducted at Indira Gandhi Medical College (IGMC), Shimla, Himachal Pradesh among the resident doctors using predesigned, structured, self-administered anonymous close-ended questionnaire. We analyzed the data using Stata software version 12. Results: There were a total of 61 study participants, who consented to participate, of which more than half were females (52.5%). The mean age of the study participants was 28.6±0.63 years. Regarding the source of knowledge about medical ethics most of the study participants had acquired the information during their experience at their workplace (42.6%). A majority of the male participants disagreed that confidentiality while providing the health care services should be abandoned (54.3%). More than 90% of the study participants agreed that incorporation of medical ethics is necessary in undergraduate curriculum. Conclusions: Incorporation of a formal structured teaching on medical ethics in the undergraduate curriculum is the need of the hour. Besides research work, the medical ethics committee in the institution should also act as the guiding hands to address the grievances faced by the doctors during medical practice.